Nonviolent Resistance and Democratic Consolidation - Lambach, Daniel. author. (orcid)0000-0003-4670-4188 Link aut Link
XI, 193 p. 11 illus.
Keywords: ‘At a time when authoritarianism is resurgent and democracy is under threat globally, this timely book shines a light on a critical but underappreciated driver of democratization: ordinary citizens.’ —Maria J. Stephan, Director, Program on Nonviolent Action, USIP, USA. ‘This insightful book is essential reading for all interested in democratization in the aftermath of conflict and how mobilization can affect how institutions evolve.’ —Kristian Skrede Gleditsch, Professor, University of Essex, UK. ‘This is an essential contribution to a fascinating interdisciplinary field which shows that unarmed resistance movements facilitate the emergence of democracy.’ — Stellan Vinthagen, Chair and Professor of Sociology, University of Massachusetts, Amherst, USA. This book argues that democracies emerging from peaceful protest last longer, achieve higher levels ofdemocratic quality, and are more likely to see at least two peaceful handovers of power than democracies that emerged out of violent resistance or top-down liberalization. Nonviolent resistance is not just an effective means of deposing dictators; it can also help consolidate democracy after the transition from autocratic rule. Drawing on case studies on democratic consolidation in Africa and Latin America, the authors find that nonviolent resistance creates a more inclusive transition process that is more resistant to democratic breakdown in the long term. Daniel Lambach is Postdoctoral Research Fellow at Goethe University, Germany. Markus Bayer is Research Fellow at University of Duisburg-Essen, Germany. Felix S. Bethke is Senior Researcher at the Peace Research Institute Frankfurt, Germany. Matteo Dressler is Researcher at the Flemish Peace Institute, Belgium. Véronique Dudouet is Programme Director at Berghof Foundation, Germany.